Yearly Trend of Syphilis Seroprevalence Among STD, ART and ANC Attendees: Six-Year Period Study from A Tertiary Care Hospital - Kashyap, Bineeta; Goyal, Nisha; Singha, Krishna; Tajuddin, Mohd; Singh, N P (Annals of Pathology and Laboratory Medicine, 2019)
Background & Objective: Despite the several ongoing campaigns highlighting the importance of safe sexual practices and public awareness activities about sexually transmitted diseases (STDs), syphilis still constitutes a significant public health problem in the developing countries. The present study was initiated to understand the current trend of syphilis among the (STD) clinic patients, patients receiving anti-retroviral treatment (ART) and antenatal mothers. Methods:This study extended over a period of six years from 2013-2018.All the samples that were sent for routine VDRL testing were included in the present study.Samples were screened by qualitative and quantitative VDRL test. Results: A total of 77,634 serum samples were screened for syphilis by VDRL testing over a period of six years. Out of these, 762 samples were reactive. Syphilisseroprevalence ranged from 0.33% to 2.19% with the highest seroprevalence in the year 2018. 75.6% of the cases belonged to 18-35 years age group. An overall upward trend of the VDRL reactive cases was recorded among all the three groups of STD, ART and antenatal clinic cases. Conclusions: It is crucial to understand the current trend and epidemiology of syphilis among ART, STIs and ANC clinic attendees for the proper planning andimplementation of preventive and control strategies.